Retrobulbar pigmented peripheral nerve sheath tumor in a dog. (1st November 2015) - Curto, Elizabeth; Clode, Alison B; Durrant, Jessica; Montgomery, Keith W; Gilger, Brian C
Abstract: A 1‐year‐old male castrated Pug was referred for unilateral exophthalmos unresponsive to oral antibiotic and anti‐inflammatory therapy. Clinical findings included exophthalmos of the left eye with lateral strabismus, resistance to retropulsion, and an elevated nictitans. Hematologic and biochemical analyses were within normal limits. Findings following computed tomography (CT) of the head included an expansile retrobulbar soft tissue mass with bony lysis extending into the left nasal cavity and nasopharynx. Ultrasound‐guided fine‐needle aspirates and biopsy samples obtained via rhinoscopy were nondiagnostic. Palliative exenteration was elected; the patient was euthanized 13 weeks following exenteration due to development of neurologic signs and perceived poor quality of life. The histopathologic diagnosis was a malignant pigmented peripheral nerve sheath tumor.